Analysis of Student Visiting Behavior to Madrasah Libraries as a Basis for Developing Literacy Services - Arini Rahmania Fadilah; Atiqotul Kamalia; Anggun Anugrah Tri Kartika Sari; Rusdiana Navlia (Penerbit Presisi Pustaka, 2026)
Madrasah libraries play a strategic role in fostering a culture of literacy among students, yet their utilization often falls far short of their potential. The purpose of this study is to examine how students visit madrasah libraries, identify factors influencing the frequency of their visits, and develop a plan for the creation of relevant and sustainable literacy services. The method used was a literature review. From 2020 to 2024, academic sources such as journal articles, official reports, and scientific publications were systematically reviewed. According to the findings, four main dimensions influence students’ library visit behavior. These include students’ personal motivation, the quality of the library’s collection and facilities, the competence of library staff, and teachers’ active involvement in integrating literacy into learning. It was found that several structural barriers, including a lack of relevant collections, uncomfortable layouts, and insufficient programs to promote literacy, act as major obstacles to building sustainable reading habits. This study found that transforming madrasah libraries into flexible learning resource centers is a crucial step. Library management, the curriculum, and the madrasah’s institutional commitment must work together.